Adverse systemic reaction to benznidazole - María Verónica Pacheco Coronel; Laura Oriente Frutos; Eva Calabuig Muñoz; Diana Kury Valle; Dolores Hernández Fernández de Rojas (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract Benznidazole, drug of choice for Chagas disease (CD), has been associated with a high incidence of adverse reactions that can become serious, necessitating discontinuation of the drug. We describe the case of a Bolivian patient living in Spain for 9 years, who, following treatment with benznidazole for CD in indeterminate chronic phase, presented with fever, skin lesions, digestive symptoms, general malaise, and laboratory abnormalities. After the discontinuation of benznidazole and, the intake of antihistamines and systemic corticosteroids, the patient presented a complete resolution of the symptoms. Optimization of dose strategies and development of more effective, and better-tolerated drugs is advisable.